DETECTION OF Lawsonia intracellularis DNA IN ILEAL TISSUES OF DEAD WILD BIRDS IN THE REPUBLIC OF KOREA - Jung-Yong Yeh; Jeong-Min Hwang; Jae Geun Kim (Slovenian Veterinary Research, 2017)
Lawsonia intracellularis is an etiological agent that causes proliferative enteropathy in various species. Little is known about the mechanisms of transmission of L. intracellularis, especially in wild bird species. The presence of L. intracellularis in dead wild birds in the Republic of Korea was investigated using the polymerase chain reaction method. L. intracellularis DNA was identified in the mucous membrane of the ileum in one Eurasian eagle-owl (Bubo bubo, Strigidae), two black-billed magpies (Pica pica sericea, Corvidae), and one jungle crow (Corvus macrorhynchos, Corvidae) among 745 dead wild birds examined. Although few wild birds in this study were exposed to L. intracellularis, the exposure was likely to be epidemiologically relevant. Regarding the ecological behavior of the bird species found to be exposed to L. intracellularis in the current study (Eurasian eagle-owl, black-billed magpie, and jungle crow), swine or horse farm facilities, which are reservoirs for L. intracellularis, might be easily accessed by such wild birds. Thus, these and similar species could have increased chances of exposure to L. intracellularis and could serve as biological vectors of proliferative enteropathy. Wild bird feeding patterns and previous reports of wild and feral animals exposed to L. intracellularis could be an alternative explanation for the association between L. intracellularis and wild birds.